Periodic structures on liquid-phase smectic A, nematic and isotropic free surfaces - Bagdinova, Anna N.; Demikhov, Evgeny I.; Borisenko, Nataliya G.; Tolokonnikov, Sergei M.; Mishakov, Gennadii V.; Sharkov, Andrei V. (Beilstein Journal of Nanotechnology, 2018)
The free boundary of smectic A (SmA), nematic and isotropic liquid phases were studied using a polarized optical microscope, an interferometric surface structure analyzer (ISSA), an atomic force microscope (AFM) and a scanning near-field optical microscope (SNOM). Images of the SmA phase free surface obtained by the polarized microscope and ISSA are in good correlation and show a well-known focal domain structure. The new periodic stripe structure was observed by scanning near-field optical microscopy on the surface of the smectic A, nematic and isotropic phases. The properties of this periodic structure are similar to the charged liquid helium surface and can be explained by nonlinear electrostatic instabilities previously described.
Keywords: focal conic domains; free boundary; liquid crystals; microscopy; smectic A phase